2016
DOI: 10.1186/s13256-016-1060-y
|View full text |Cite
|
Sign up to set email alerts
|

Successful switch from enzyme replacement therapy to miglustat in an adult patient with type 1 Gaucher disease: a case report

Abstract: BackgroundGaucher disease is one of the most common lipid-storage disorders, affecting approximately 1 in 75,000 births. Enzyme replacement therapy with recombinant glucocerebrosidase is currently considered the first-line treatment choice for patients with symptomatic Gaucher disease type 1. Oral substrate reduction therapy is generally considered a second-line treatment option for adult patients with mild to moderate Gaucher disease type 1 who are unable or unwilling to receive lifelong intravenous enzyme in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 42 publications
0
1
0
Order By: Relevance
“…Implementation of this strategy is called substrate reduction therapy (SRT) [9]. The efficiency of this rationale has been observed using the flavonoid genistein (5,7-dihydroxy-3-(4-hydroxyphenyl)-4 H -1-benzopyran-4-one) in Sanfilippo disease, and miglustat (Zavesca ® ) in Gaucher disease [10]. Many investigations have revealed that due to pleiotropic effects, genistein can be used to modulate pivotal mechanisms in human cells, for instance, the cell cycle [11], metabolism of macromolecules [12] or biogenesis and activity of lysosomes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of this strategy is called substrate reduction therapy (SRT) [9]. The efficiency of this rationale has been observed using the flavonoid genistein (5,7-dihydroxy-3-(4-hydroxyphenyl)-4 H -1-benzopyran-4-one) in Sanfilippo disease, and miglustat (Zavesca ® ) in Gaucher disease [10]. Many investigations have revealed that due to pleiotropic effects, genistein can be used to modulate pivotal mechanisms in human cells, for instance, the cell cycle [11], metabolism of macromolecules [12] or biogenesis and activity of lysosomes [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…ERT aids the body in recycling more waste material, specifically GlcCer, whereas SRT helps the body generate less of this waste material. SRT does not rely on enzyme replacement but instead reduces the accumulation of glycolipids by balancing the residual activity of the deficient enzyme with lowered substrate levels 123 . Recent studies have shown that SRT- oral miglustat, which also can cross BBB 124 , may be more effective than ERTs in reducing the size of the spleen and liver, improving bone density, and reducing levels of the biomarker chitotriosidase 123 .…”
Section: Current Therapeuticsmentioning
confidence: 99%
“…SRT does not rely on enzyme replacement but instead reduces the accumulation of glycolipids by balancing the residual activity of the deficient enzyme with lowered substrate levels 123 . Recent studies have shown that SRT- oral miglustat, which also can cross BBB 124 , may be more effective than ERTs in reducing the size of the spleen and liver, improving bone density, and reducing levels of the biomarker chitotriosidase 123 . SRT venglustat with the potential of crossing BBB can alleviate the symptoms and prevent disease progression 125 .…”
Section: Current Therapeuticsmentioning
confidence: 99%